Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/978-3-319-72709-7_10
|View full text |Cite
|
Sign up to set email alerts
|

Near-Fault Broadband Ground Motion Simulations Using Empirical Green’s Functions: Application to the Upper Rhine Graben (France–Germany) Case Study

Abstract: Seismic hazard estimation relies classically on data based ground motion prediction equations (GMPEs) giving the expected motion level as a function of several parameters characterizing the source and the sites of interest. However, records of moderate to large earthquakes at short distances from the faults are still rare. For this reason, it is difficult to obtain a reliable ground motion prediction for such a class of events and distances where also the largest amount of damage is usually observed. A possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…A study is presently ongoing in the Upper Rhine Graben to better constrain the recent activity of the fault system (Baize et al, 2016) based on geophysical and palaeoseismological investigations. An additional study (Del Gaudio et al, 2016) is modelling ground motion in the Upper Rhine Graben with the help of the empirical green function approach (Del Gaudio et al, 2015). It is hoped that these studies will provide new insights for reducing epistemic uncertainty in faultbased PSHA of the Upper Rhine Graben.…”
Section: Perspectivesmentioning
confidence: 99%
“…A study is presently ongoing in the Upper Rhine Graben to better constrain the recent activity of the fault system (Baize et al, 2016) based on geophysical and palaeoseismological investigations. An additional study (Del Gaudio et al, 2016) is modelling ground motion in the Upper Rhine Graben with the help of the empirical green function approach (Del Gaudio et al, 2015). It is hoped that these studies will provide new insights for reducing epistemic uncertainty in faultbased PSHA of the Upper Rhine Graben.…”
Section: Perspectivesmentioning
confidence: 99%
“…The primary goal of this work is to identify the Strong Motion Ground Acceleration (SMGA) that most accurately mimics the broadband ground motions at a certain distance. In order to forecast broadband ground-motion time histories, we employed the Extended k-2 Source model (Causse et al 2009;Dujardin et al 2016Dujardin et al , 2018Del Gaudio et al 2018) and combined it with the EGF (Hartzell, 1978) approach, based on a number of small events by taking radiation pattern adjustments into consideration. Numerous publications have indicated that this method is effective at replicating ground motion for various places (Causse et al 2021;Castro-cruz et al 2021;Dujardin et al 2019;Del Gaudio et al 2018;Del Gaudio et al 2015).…”
mentioning
confidence: 99%